Pedagogiczno-psychologiczne aspekty zapobiegania agresji na etapie szkolnym = Pedagogical and psychological aspects of prevention of agression at school stage - Drumińska, Ewelina; Wojdat, Marta; Pujszo, Małgorzata; Stępniak, Robert (Journal of Education, Health and Sport, 2016)
Drumińska Ewelina, Wojdat Marta, Pujszo Małgorzata, Stępniak Robert. Pedagogiczno-psychologiczne aspekty zapobiegania agresji na etapie szkolnym = Pedagogical and psychological aspects of prevention of agression at school stage. Journal of Education, Health and Sport. 2016;6(8):595-606. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.61003 http://ojs.ukw.edu.pl/index.php/johs/article/view/3790 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 01.08.2016. Revised 08.08.2016. Accepted: 26.08.2016. Pedagogiczno-psychologiczne aspekty zapobiegania agresji na etapie szkolnym Pedagogical and psychological aspects of prevention of agression at school stage Drumińska Ewelina1, Wojdat Marta1, Pujszo Małgorzata1, Stępniak Robert2 1 Studenckie Koło Naukowe "WyKoNa", Uniwersytet Kazimierza Wielkiego, Bydgoszcz, Polska 2 Instytut Kultury Fizycznej, Uniwersytet Kazimierza Wielkiego, Bydgoszcz, Polska Corresponding author: Stępniak Robert Ph. D Instytut Kultury Fizycznej, Uniwersytet Kazimierza Wielkiego, ul. Sportowa 2, 85-091 Bydgoszcz Polska email: robi1969@wp.pl Słowa kluczowe: zapobieganie agresji, sporty walki młodzież. Keywords: prevention of agression, martial arts, youth. Streszczenie Cel: Zjawisko agresji w środowisku szkolnym stanowi istotny problem współczesnej pedagogiki. Jest więc sprawą oczywistą, że lepiej jest zapobiegać agresji niż walczyć z jej skutkami. Sporty walki adoptowane do szkolnictwa wraz z całą nadbudowa pedagogiczno- psychologiczną kodeksu honorowego Budo rozwijają tężyznę fizyczną młodego pokolenia narzucając jednocześnie twarde zasady moralne. W niniejszych badaniach postanowiono sprawdzić czy trening różnych sportów walki aplikowany w danym środowisku szkolnym daje możliwość kontrolowania własnej agresji. Materiał i metody: W badaniach wzięło udział 28 uczniów trenujących w środowisku szkolnym różne sporty walki oraz 28 uczniów ćwiczących jedynie na zajęciach obowiązkowych. Poziom agresji sprawdzono za pomocą kwestionariusza agresji Buss-Perry - Instytut Amity. Wyniki: Zebrane dane wykazały obniżony poziom agresji całkowitej, oraz spadek agresji całkowitej w funkcji stażu treningowego w grupie uczniów trenujących sporty walki. Nie wszystkie elementy składowe agresji trenujących uczniów ulegały jednak obniżeniu. Wnioski: Trening sportów walki realizowany z dziećmi/młodzieżą szkolną stanowi dobry, lecz jedynie początkowy etap zapobiegania agresji w warunkach szkolnych. Abstract Objective: The phenomenon of agression in the school environment is an important issue of modern pedagogy. It is so obvious that it is better to prevent an agression than to correct its consequences. Martial arts adapted to the school along with the entire superstructure of pedagogical and psychological code of honor Budo develop physical prowess of the younger generation at the same time imposing tough moral principles. In the present study it was decided to check the training of various martial arts applied in the school environment gives you the ability to control their own aggression. Material and Methods: The study involved 28 students who training in the school environment, various martial arts, and 28 students practicing only mandatory Physical Education. The level of aggression was examined by questionnaire aggression Buss-Perry - Amity Institute. Results: The collected data showed a reduced level of total aggression, and a decrease in total aggression as a function of training experience in a group of student training in martial arts. But not all components of total aggression of training students were reduced Conclusions: The training of martial arts implemented with children of school is good method, but only as a initial start of the prevention of agression in the school environment.